Advanced Ovarian Pregnancy: A Case Report of Misdiagnosis and Surgical Outcomes - Noppamart Whangteeranon; Pang Pinyochotiwong (Case Reports in Obstetrics and Gynecology)
Background. Ovarian pregnancy is rare and difficult to diagnose preoperatively, especially in advanced gestational age. Misdiagnosis can increase the chance of emergent complications. Case. A misdiagnosed case of a 33-week ovarian pregnancy woman who underwent surgery due to a preoperative diagnosis of a dead fetus in utero, and transverse lie was reported with eventful surgical outcomes. This case resulted in the delivery of a dead fetus and a sudden massive hemorrhage that occurred after placental detachment. Oophorectomy could not be performed due to severe bowel adhesions and multiple feeding vessels from the bowel at the posterior part of the left ovary. The placental site was sutured at multiple sites, and local hemostatic agents were placed for hemostasis. Postoperatively, she received multiple transfusions and was safely discharged after 10 days. Conclusion. Obstetricians must be acutely aware of this condition, especially while performing sonography preoperatively, for better outcomes.